2016
DOI: 10.1108/jap-03-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Putting people at the centre: facilitating Making Safeguarding Personal approaches in the context of the Care Act 2014

Abstract: The Journal of Adult Protection 1 | P a g e Putting people at the centre: facilitating Making Safeguarding Personal approaches in the context of the Care Act 2014 Abstract PurposeThe purpose of this paper is to describe and discuss the pilot Making Safeguarding Personal (MSP) project that ran in three London Boroughs in England in 2014-2015. The project aimed to help local authority social work practitioners better engage with adults at risk at the beginning, middle and end of safeguarding work and to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…in their review of MSP, identified differing views of what constitutes a 'good outcome' among Adult Safeguarding Leads (ASL) and between ASL and service users. WhilstButler et al (2016) and Timpson et al…”
mentioning
confidence: 99%
“…in their review of MSP, identified differing views of what constitutes a 'good outcome' among Adult Safeguarding Leads (ASL) and between ASL and service users. WhilstButler et al (2016) and Timpson et al…”
mentioning
confidence: 99%
“…It may also reflect subtle but powerful inequalities in the ‘credibility economy’ in which knowers and listeners interact. In the UK, health and social care professionals work within a policy and legislative framework that emphasises individuals’ rights to self‐determination and the need to protect and prioritise the needs of adults requiring care (Butler and Manthorpe ). Whilst there may be a clear ethical and legal basis for this position it is nevertheless possible to see how, in some situations, this perspective can lead to carers’ needs being unintentionally rendered less visible, particularly if carers’ views seemingly contradict or undermine the needs and wishes of the person for whom they care.…”
Section: Resultsmentioning
confidence: 99%
“…This person-centred approach to adult safeguarding is also a key feature, and success, of Making Safeguarding Personal (Butler and Manthorpe, 2016), which is also now a requirement under the Care Act Statutory Guidance (Department of Health, 2016, para.14.14-14.15). Likewise, paragraph 14.11 of the Care and Support Statutory Guidance (Department of Health, 2016), for example, states that one of the aims of the adult safeguarding provisions is to “safeguard adults in a way that supports them in making choices and having control about how they want to live”, and furthermore, at paragraph 14.39-14.40, that:It is important to understand the circumstances of abuse, including the wider context such as whether others may be at risk of abuse, whether there is any emerging pattern of abuse, whether others have witnessed abuse and the role of family members and paid staff or professionals […] The circumstances surrounding any actual or suspected case of abuse or neglect will inform the response.…”
Section: “Adult At Risk”: Vulnerability By Any Other Name?mentioning
confidence: 99%
“…In the statutory guidance to the Care Act, for example, any safeguarding response should be based on the six principles; empowerment, prevention, proportionality, protection, partnership, and accountability (Department of Health, 2016, para.14.12). Moreover, the guidance also makes clear that any adult safeguarding enquiry and response should be person-focused, take into consideration the circumstances of that particular adult, and driven This person-centred approach to adult safeguarding is also a key feature, and success, of Making Safeguarding Personal (Butler and Manthorpe, 2016), which is also now a requirement under the Care Act Statutory Guidance (Department of Health, 2016, para.14.14-14.15). Likewise, paragraph 14.11 of the Care and Support Statutory Guidance (Department of Health, 2016), for example, states that one of the aims of the adult safeguarding provisions is to 'safeguard adults in a way that supports them in making choices and having control about how they want to live', and furthermore, at paragraph 14.…”
Section: Concern Was Also Voiced During Thementioning
confidence: 99%